Deals and Development: The Political Dynamics of Growth Episodes - Kunal Sen; Lant Pritchett; Eric Werker (Oxford University Press, 2018)
When are developing countries able to initiate periods of rapid growth and why have so few of these countries been able to sustain growth over decades? Deals and Development: The Political Dynamics of Growth Episodes seeks to answer these questions and many more through a novel conceptual framework built from a political economy of business–government relations. Economic growth for most developing countries is not a linear process. Growth instead proceeds in booms and busts, yet most frameworks for thinking about economic growth are built on the faulty assumption that a country's economic performance is largely stable. Deals and Development explains how growth episodes emerge and when growth, once ignited, is maintained for a sustained period. It applies its new framework to examining the growth of countries across a range of institutional and political contexts in Africa and Asia, using the examples of Bangladesh, Cambodia, India, Malaysia, Thailand, Ghana, Liberia, Malawi, Rwanda, and Uganda. Through these country analyses it demonstrates the explanatory power of its framework and the importance of feedback cycles in which economic trends interact with political behaviour to either sustain or terminate a growth episode. Offering a lens through which to analyse complex scenarios and unwieldy amounts of information, this book provides actionable levers of intervention to bring around reform and improve a country's chance at achieving transformative economic growth.
Keywords: 330; economic growth; political settlements; deals environment; rent space; structural transformation; policy